Quality Management Essentials - Popov, Ivan (London: World Scientific, 2025)
A product's design is based on what customers want and how much they are willing to pay for it determines its quality. The production process is supposed to achieve the required quality. Due to the natural process variation the quality of a product or service varies. Thus, quality can be defined as fitness for intended use or, in other words, how well the product performs its intended function. It is a written or unwritten commitment to a known or unknown consumer in the market. Quality management ensures that a product or service is fit for its purpose. It has three main components: quality planning, quality control and quality improvement. Quality management is focused not only on product and service quality, but also on the means to maintain it. Quality management, therefore, uses quality control tools to achieve more consistent quality.
Includes Appendices, references and index
Keywords: Total quality management; Quality control; Industrial management; Quality assurance